CAPTURING THE CONSUMER EXPERIENCE USING THE HCBS CAHPS SURVEY: CONNECTICUT'S USE & ADOPTION ACROSS MULTIPLE WAIVERS. (11th November 2018) - Gruman, C; Tucker, K; Bruni, K; Lambert, D; Robison, J
Abstract: As states shift towards greater use of community-based long-term services and supports rather than institution-based care, they face challenges in measuring and using consumer experience and service quality measures. The 2010 Patient Protection and Affordable Care Act (ACA) included many incentives for states to build capacity in their CB-LTSS systems and standardize quality measures. In response to Section 2701, CMS awarded planning grant funds to nine states interested in participating in Testing Experience and Functional Tools (TEFT). The HCBS CAHPS Survey was developed as a cross-disability tool that focuses on participant experience as opposed to satisfaction and addresses how a beneficiary values the quality of services received. The cross-disability focus is unique compared to other experience and satisfaction surveys as individuals with different disabilities (e.g., those with physical, cognitive, intellectual, or behavioral disabilities who receive Medicaid funded HCBS) can respond to the same questionnaire, thus allowing for comparisons across programs and disability groups. Connecticut, one of nine TEFT grantees, played an important role in the testing phases required for CAHPS trademark designation and eventual cross-agency adoption of the survey. Activities included, but were not limited to, field testing the survey with over 1, 000 beneficiaries, developing several ways to facilitate the inclusion of any eligible participant who wanted to complete the survey including providing iPads to participants with speech challenges like aphasia. Ongoing data collection will be used for internal quality monitoring, quality improvement, and performance based payments. Suggestions for scalability and cross-waiver adoption will be discussed during the presentation.